Vriesea badinii (Bromeliaceae, Tillandsioideae), a new species from Ouro Preto, Minas Gerais, Brazil - Guarçoni, Elidio Armando Exposto; Costa, Andrea Ferreira Da; Kessous, Igor Musauer (Phytotaxa, 2025)
This study describes and illustrates a new species of Vriesea, V. badinii, from the quarzitic campos rupestres of the Serra do Espinhaço. This species occurs in areas above 1,500 m, on the edges of the ruins of the Estrada Real in Serra do Chafariz, Ouro Preto, Brazil. The new species is related to a complex of species that share ecological preferences and exhibit convergence in leaf rosette morphology, resulting in a similar overall appearance. This group comprises yellow-flowered, rupicolous species found on isolated mountain tops in southeastern Brazil. Morphologically, the new species is compared with V. claudiana, V. stricta, V. marceloi and V. clausseniana. However, Vriesea badinii and V. clausseniana show the greatest similarity, as they are both nocturnal flowering chiropterophilous species, with a campanulate corolla and obovate-spatulate petals. Images of the plants in the habitat, photos of the holotype and a morphological comparison table are provided.